DCS platform-based embedded DSP intelligent optimizing control method and DCS platform-based embedded DSP intelligent optimizing control device - LI PEIRAN; WANG LEI; YAN WENJUN; ZHANG JINFENG; MENG XUN; ZHENG JUN (2010)
The invention discloses a DCS platform-based embedded DSP intelligent optimizing control method and a DCS platform-based embedded DSP intelligent optimizing control device. A DCS control cabinet is taken as a bridge for connecting field equipment and a DSP embedded control platform; a DSP application board is connected with the field equipment through the DCS control cabinet to map a signal on an input terminal of the DSP application board to an output terminal by utilizing a digital signal on a conventional I/O terminal in the DCS control cabinet, and then the output terminal is connected to a conditioning circuit to condition the output signal into a signal range which can be accepted by a DSP development board; the DSP application board stores values of control variables needing acquiring into a memory of the DSP application board through a high-speed data acquisition port; data is processed through a pre-embedded intelligent control algorithm, and processing results are output through the conditioning cir